Citations to Wikipedia in Chemistry Journals: A Preliminary Study. - Bradley Brazzeal (Issues in Science and Technology Librarianship)
Wikipedia has been the subject of an increasing number of studies. Many of these have focused on the quality of Wikipedia articles and the use of Wikipedia by students. Little research has focused on the use of Wikipedia by scholars. This study helps to fill that gap by examining citations to Wikipedia in chemistry journals from three major publishers over a five year period. The study reports the number of citations to Wikipedia and describes how Wikipedia is being cited. The results show that, while only a small percentage of all articles contained a citation to Wikipedia, it is in fact being cited as a credible information source in articles in major chemistry journals. [ABSTRACT FROM AUTHOR]